2018
DOI: 10.1515/adms-2017-0040
|View full text |Cite
|
Sign up to set email alerts
|

The effect of shot peening on the corrosion behaviour of Ti-6Al-4V alloy made by DMLS

Abstract: Additive Manufacturing processes are being used increasingly in the scope of medicine and dentistry. As indicated by literature data, the durability and quality of medical implants is decisively influenced by surface modification. Insufficient quality of surface finishing leads, among others, to reduced service life of applied implants and to increased number of necessary revision surgeries. Furthermore, various types of finishing processes e.g. cleaning, shot peening or abrasive techniques are suggested by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…Titanium alloys are protected as a result of thin passive layer spontaneously developing on their surface. The passive layer created on surgical Ti-6Al-4V alloys is stable in body fluids solution, and rich mainly in amorphous TiO 2 [4,29,37]. The thickness of such passive films is usually equal to a few nanometres, but they constitute a highly protective barrier between the metallic alloy surface and the aggressive environment of body fluids.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Titanium alloys are protected as a result of thin passive layer spontaneously developing on their surface. The passive layer created on surgical Ti-6Al-4V alloys is stable in body fluids solution, and rich mainly in amorphous TiO 2 [4,29,37]. The thickness of such passive films is usually equal to a few nanometres, but they constitute a highly protective barrier between the metallic alloy surface and the aggressive environment of body fluids.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of the shot peening process, a rough surface is created which is susceptible to corrosion in connection with destroyed areas of the passive film as a result of the shot impact [28,29]. However, Jelliti et al [4] observed the creation of a stable passive film, and the increase of electrochemical potential on titanium specimens subjected to the shot peening process.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[68][69][70][71][72][73][74][75][76] • Mechanical surface finishing (planar polishing, tumble polishing, etc.) 20,33,35,40,43,44,[77][78][79][80][81][82] • Chemical polishing 83,84 • Investigating multiple techniques, separate and combined 78,85,86 All techniques showed reductions in surface roughness of the AM parts, yet an issue for many of them is their inability to effectively polish a complex shaped part. Electropolishing presents itself as a sound method to polish complex shapes, with current studies by Urlea et al on building customized cathodes adjacent to an AM part to improve polishing efficiency 64,65 .…”
mentioning
confidence: 99%